Observation of anomalous spectral downshifting of waves in the Okhotsk Sea Marginal Ice Zone - Takuji Waseda; Alberto Alberello; Takehiko Nose; Takenobu Toyota; Tsubasa Kodaira; Yasushi Fujiwara (2022)
A table and a figure providing supplementary observational data.